1978
DOI: 10.1111/j.1748-1716.1978.tb06083.x
|View full text |Cite
|
Sign up to set email alerts
|

Urinary cyclic AMP and vasopressin excretion in rat strains selected for their alcohol intake

Abstract: Urinary excretion of adenosine 3',5' -cyclic monophosphate (cAMP) and immunoreactive arginine vasopressin (AVP) were investigated after water loading and following ethanol loading in two rat strains selected for their voluntary ethanol intake. After ethanol loading ethanol preferring (AA) rats excreted more cAMP but less AVP than water preferring (ANA) rats. The results suggest that the strain difference in cAMP excretion is of renal origin and is not due to vasopressin or parathormone. Differences in the symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…When comparing alcoholics to more alcohol naïve individuals, alcoholics were found to have a more pronounced decrease in plasma VP levels when drinking (Collins et al 1992; Hirschl et al 1994), suppressed VP levels even during alcohol withdrawal (Doring et al 2003; Hirschl et al 1994; Jahn et al 2004; Trabert et al 1992), and a lack of a VP increase in response to novelty (Ehrenreich et al 1997). Similarly, differences in urine VP (urine VP being an approximate measure of plasma VP) are found between alcohol preferring (AA rats) and alcohol non-preferring rats (ANA) (Linkola and Fyhrquist 1978; Linkola et al 1977). However the two studies do not agree on the directionality of the difference as one study found a decrease in urine VP in AA rats compared to ANA rats and the other an increase in urine VP in AA rats compared to ANA rats.…”
Section: Alcohol’s Effect On the Vp Systemmentioning
confidence: 97%
“…When comparing alcoholics to more alcohol naïve individuals, alcoholics were found to have a more pronounced decrease in plasma VP levels when drinking (Collins et al 1992; Hirschl et al 1994), suppressed VP levels even during alcohol withdrawal (Doring et al 2003; Hirschl et al 1994; Jahn et al 2004; Trabert et al 1992), and a lack of a VP increase in response to novelty (Ehrenreich et al 1997). Similarly, differences in urine VP (urine VP being an approximate measure of plasma VP) are found between alcohol preferring (AA rats) and alcohol non-preferring rats (ANA) (Linkola and Fyhrquist 1978; Linkola et al 1977). However the two studies do not agree on the directionality of the difference as one study found a decrease in urine VP in AA rats compared to ANA rats and the other an increase in urine VP in AA rats compared to ANA rats.…”
Section: Alcohol’s Effect On the Vp Systemmentioning
confidence: 97%